Boosting Textile Industry Growth: Adversity Quotient Meets Entrepreneurial Orientation - Handiman, Unang Toto; Irawan, Towaf Totok; Kimpah, Jeniboy; Sukardiman, Diah Fistiani (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: The worldwide market presents substantial problems for the textile sector, especially for small and medium-sized businesses. This study explores how business performance in Java Islands SMEs' textile sectors is impacted by the Adversity Quotient (AQ) and Entrepreneurial Orientation (EO). This study focuses to determine how resilience and entrepreneurial behaviour affect organisational performance using a resource-based view.Methodology: Data were collected from 277 respondents across various SME textile firms through structured questionnaires. Structural equation modelling (SEM) was utilised to analyse the data to validate the suggested connections between AI, EO, and firm performance.Finding: The findings reveal that both AQ and EO significantly impact firm performance. Specifically, AQ boost the firm's capacity to navigate challenges and exploit opportunities, while EO fosters for competitive edge. The inestigation highlights that EO mediated partially the association among AQ along firm performance, suggesting that entrepreneurial behaviors amplify the significant effects of resilience on organizational outcomes.Conclusion: These results offer valuable insights for SME textile firms, figuring the valuable of cultivating high AQ and nurturing an entrepreneurial culture to improve performance. The study participates to the conceptual grasp of AQ and EO within the confine of emerging markets and provides practical recommendations for industry stakeholders to enhance their competitive